2017
DOI: 10.1016/j.tcs.2017.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Terminal embeddings

Abstract: In this paper we study terminal embeddings, in which one is given a finite metric (X, d X ) (or a graph G = (V, E)) and a subset K ⊆ X of its points are designated as terminals. The objective is to embed the metric into a normed space, while approximately preserving all distances among pairs that contain a terminal. We devise such embeddings in various settings, and conclude that even though we have to preserve ≈ |K| · |X| pairs, the distortion depends only on |K|, rather than on |X|.We also strengthen this no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…In [EFN17,MMMR18] and the current work, a terminal embedding is obtained by, for each u ∈ R d \X, defining an outer extension f Ext act identically on X for any u, u ′ ∈ R d , we can then define our final terminal embedding bỹ…”
Section: Overview Of Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…In [EFN17,MMMR18] and the current work, a terminal embedding is obtained by, for each u ∈ R d \X, defining an outer extension f Ext act identically on X for any u, u ′ ∈ R d , we can then define our final terminal embedding bỹ…”
Section: Overview Of Approachmentioning
confidence: 99%
“…They called such an embedding a terminal embedding 1 . Though rather than achieving terminal distortion 1 + ε, their work only showed how to achieve constant terminal distortion with m = O(log n) for a constant that could be made arbitrarily close to √ 10 (see [EFN17,Theorem 1]). Terminal embeddings can be useful in static high-dimensional computational geometry data structural problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps surprisingly, Coppersmith and Elkin showed that nontrivial linear size distance preservers do indeed exist: in any undirected graph, one can preserve any p = O(n 1/2 ) pairwise distances using a subgraph on just O(n) edges. This unexpected fact has found several interesting applications: for example, Elkin and Pettie [26] used it to build the first linear-size log n stretch path reporting distance oracle, Bodwin and Vassilevska W. [13] have used it to build the current most accurate additive spanner of linear size, Pettie [38] used them as an ingredient in state-of-the-art constructions for mixed spanners, and they were employed by Elkin, Filtser, and Neiman [24] to build terminal subgraph spanners.…”
Section: Historymentioning
confidence: 99%
“…The constant loss in the first part of the scheme has to do with an outer extension, implicitly developed in [EFN17], and explicated in [MMMR18,NN19]. Bi-Lipschitz outer extensions have been a focus of recent research [MMMR18,NN19,EN18], where they were studied in the context of Johnson-Lindenstrauss dimension reduction [MMMR18,NN19], and in the context of doubling metrics [EN18].…”
Section: Introductionmentioning
confidence: 99%